The mixture of biobutanol and petrol for Otto engines - Pukalskas, Saugirdas; Bogdanovičius, Zenonas; Sendžikienė, Eglė; Makarevičienė, Violeta; Janulis, Prutenis (Transport, 2009)
The expansion of production and the use of biofuels are determined by the legal acts of the European Commission and National legal acts encouraging such production and usage. It would be meaningful to use the mixtures of butanol and petrol in Otto engines. It was determined the possibility of producing biobutanol as a biofuel of the second generation from lignocellulose hydrolyzed to C5/C6 carbohydrates. If the 20–30% potential of lignocellulose biomass in Lithuania is used, it would be possible to produce 200–300 thousand t of biobutanol per year. The amount of carbon monoxide CO decreases by more than 80% when the engine works using the mixtures of petrol and butanol if compared to the CO amount of the engine working with petrol. When the engine works using the mixture of 30% butanol and petrol, the amount of carbon dioxide CO2decreases by 4% on average, and in case it works with the mixture of 50% butanol and petrol ‐ by 14% if compared to the CO2 amount of the engine working using petrol. When the engine works using the mixture of 30% butanol and petrol, the amount of hydrocarbons HC decreases by 26% on average, and if it works with the mixture of 50% butanol and petrol, the amount increases by some 4% if compared to the HC amount of the engine working using petrol. To generalize the results of the performed experiment, it is possible to state that the optimal mixture would consist of 70% petrol and 30% biobutanol.First published online: 27 Oct 2010